Hand-Dug Well Water and Waterborne Diseases in Lubumbashi, DR Congo - Manun’Ebo, Manu F.; Manya, Tsheko; Abedi, Amina; Nkulu-wa-Ngoie, Choudelle; Mutelo, Cathy Kona; Bukasa, Alex N’Kashama (British Journal of Healthcare and Medical Research, 2026)
This cross-sectional investigation was conducted in the Savio health Area, within Tabacongo Neighbourhood, a peri-urban area of Lubumbashi City in the Democratic Republic of the Congo. The researchers carried out face-to-face interviews with heads of 121 households utilizing a structured questionnaire. The study examined variables such as the use of well water, hygiene practices related to containers and hand-dug wells, and the proximity of the well from sanitation facilities in relation to the incidence of waterborne diseases. Among the participants, 56% were women; the average age was 46 years, and 42% had attained secondary education or higher. Trading emerged as the predominant occupation, accounting for 46% of respondents. The results indicated that 64% of households reported instances of diarrhoea, 62% noted cases of typhoid fever, and 19% experienced cholera. The analysis identified a relationship between well water usage and diarrhoea, typhoid fever and intestinal parasitosis, mediated through multiple factors, including the well proximity to potential sources of contamination, and user practices in handling the water. The utilization of hand-dug well water combined with inadequate cleanliness standards for both containers and wells significantly increases the risk of illness from these diseases. This research underscores the urgent need to enhance hygiene practices and improve management of water sources to reduce disease incidence. Further investigations incorporating bacteriological testing are essential for a more comprehensive understanding of contamination pathways.